Upaya Peningkatan Output Produksi menggunakan Metode Palmer dan CDS pada PT. X - Michael Limanto (Jurnal Titra, 2022)
PT. X is a furniture company whose production system applies a make to order system. The production process of PT. X's products starts from raw materials, namely wooden boards which are processed into finished goods such as tables, chairs, and cabinets. The problems that occur in PT. X is the process of fulfilling customer orders that often experience delays. This happens because there is no scheduling system in the Woodworking Processing department, causing the production output to not reach the required production capacity. Therefore, this research was conducted to increase production output at PT. X, especially in the Woodworking Processing department. Increased production output is done by minimizing the time of the production process with the scheduling method of Campbell Dudek Smith (CDS) and Palmer. Based on the results of the research that has been done, the scheduling process using the Campbell Dudek Smith (CDS) and Palmer method is able to produce a proposal with a reduced makespan value of 32.07 seconds per wooden plank when compared to the initial conditions. By implementing a proposal that has a smaller makespan value, it is expected to increase production output so as to reduce the occurrence of delays in order fulfillment.